1990
DOI: 10.1111/j.1432-1033.1990.tb19476.x
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and characterization of a barley 1,3‐1,4‐β‐glucanase gene

Abstract: The barley gene encoding isozyme I of 1,3‐1,4‐β‐glucanase was isolated and sequenced. The 6260‐bp region sequenced included 1885 bp of the 5′‐flanking region, the entire coding region, an intron of 2490 bp, and 792 bp of the 3′‐flanking region. The 1,3‐1,4‐β‐glucanase mRNA was found to be regulated at the level of RNA accumulation by both gibberellins (positively) and abscisic acid (negatively) in barley aleurones. The mRNA for isozyme II preferentially accumulated (70%) relative to the mRNA for isozyme I (30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…1). Primer extension analyses have also indicated that isoenzyme EII mRNA is more abundant than isoenzyme EI mRNA in grain extracts that included material from both the scutellum and aleurone (18). The participation of both the aleurone and scutellum in the secretion of (1--3,1-4)-fl-glucanases, together with the spatial and temporal patterns of expression, are consistent with observed patterns of cell wall degradation in the endosperm (7).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…1). Primer extension analyses have also indicated that isoenzyme EII mRNA is more abundant than isoenzyme EI mRNA in grain extracts that included material from both the scutellum and aleurone (18). The participation of both the aleurone and scutellum in the secretion of (1--3,1-4)-fl-glucanases, together with the spatial and temporal patterns of expression, are consistent with observed patterns of cell wall degradation in the endosperm (7).…”
Section: Discussionmentioning
confidence: 55%
“…The genes encoding barley (1--3,1--4)-l3-glucanase isoenzymes EI and EII have recently been isolated and characterized (18,24,28) together with near full-length cDNAs for both isoenzyme EI and EII (24). Although the two genes exhibit a high degree of sequence identity in their 5' untranslated and protein-coding regions, their sequences diverge dramatically in the 3' untranslated region (24).…”
mentioning
confidence: 99%
“…Both enzymes have 306 amino acids and pl values greater than 10 (Hcj etaL, 1989a;Woodward and Fincher, 1982a). Further, full-length cDNAs for both have been cloned and have allowed the complete primary sequences of the enzymes to be defined Hcj et al, 1989a;Litts et a/., 1990;Slakeski et al, 1990;Wolf, 1991).…”
Section: The Case For Common Ancestrymentioning
confidence: 99%
“…)3,1~4)-,8-glucanase genes are transcribed in several tissues, and expression of the genes is likely to be under tight hormonal control. Indeed, total (l--.~3,1--+4)-/3-glucanase mRNA levels for the two isoenzymes are increased by gibberellic acid (GA.0 in isolated aleurone layers [4,9] and this reflected in en- hanced secretion of enzymic activity [2]. Auxins also mediate several physiological processes that are related to cell wall metabolism during plant development.…”
Section: Introductionmentioning
confidence: 99%
“…In germinated grain the enzymes are synthesized de novo and secreted into the starchy endosperm where they depolymerize the (1.-.->3,1 --~4)-,6'-glucans that constitute up to 70% of endosperm cell walls [3]. Expression of the two (1--93,1.-04)-,8-glucanase genes, as measured by the accumulation of their corresponding mRNAs, occurs in both the aleurone and scutellar epithelium [1,[4][5][6][7]. The expression of these two genes is subject to spatial and temporal co-ordination within the grain [1,5], Expression of (1--+3,1---)4)-,6-glucanase has al:~o been detected in young leaves and roots of the barley seedling [1,7].…”
Section: Introductionmentioning
confidence: 99%